Antioxidant and Antiproliferative Activities of Cyanidin‐3‐O‐Glucoside (C3G) Liposome in Caco‐2 Cells Cultivated in 2D and 3D Cell Culture Models. Issue 6 (29th May 2019) - Liang, Tisong; Tao, Qingfeng; Guan, Rongfa; Cao, Guozhou; Shen, Haitao; Liu, Zhenfeng; Xia, Qile
Abstract : Abstract: The aim of this study was to obtain adequate and detailed information about the antioxidant and antiproliferative activities of C3G and C3G liposomes in different cell culture models. The Caco‐2 cells were cultured in 2D and 3D cell culture models, the H2 O2 was used to construct the cell damage model and then the cells treated with C3G and C3G liposomes. The antioxidant activity and antiproliferative activities of C3G liposomes on Caco‐2 cells were investigated. We observed the morphology of cells and measured the cell viability, the activity of glutathione (GSH), superoxide dismutase (SOD), total antioxidant capacity (T‐AOC), and the content of malondialdehyde (MDA) in Caco‐2 cells treated with H2 O2, C3G, and C3G liposomes. The results showed that the Caco‐2 cells cultured in the 3D culture model formed a 3D structure and tight spheroids and showed the increase of cell activity in 3D cell culture model, compared with the 2D cell culture model. The C3G and C3G liposomes can enhance the activities of GSH, SOD, and T‐AOC but decrease the MDA content after H2 O2 treatment, while the changes were different in 2D and 3D cells culture models. This study revealed that the results obtained from the 2D cell model may be inaccurate compared with the results obtained from the 3D cell model. Practical Application: The results of this study showed that the results obtained from the 2D cell model may be inaccurate compared with the results obtained from the 3D cell model. Our work provides a method for evaluating antioxidant activity of C3G liposomes in different cell models and provided certain theoretical basis for the follow‐up research.